Pyometra Treatment by Histeropexy with Toggles Aplication in Mini Horse - Silva, Jéssica Rodrigues; Souto, Ana Paula Fadel; Strugava, Lucimara; Busato, Eduarda Maciel; Weiss, Romildo Romulado; Moreno, Juan Carlos Duque; Dornbusch, Peterson Triches (Acta Scientiae Veterinariae, 2021)
Background: Brazil is an important horse breeder that creates about three million jobs and movements about R$16,15billions per year. Although, it is important to the horse breeding industry success that the animals reproductive performance be kept. The mare pregnancy loss causes abundant forfeitures to horse breeders, furthermore, the chronic pyometra is one of that causes. The chronic pyometra is an uncommon mare condition, clinical treatments are often ineffective, under those circumstances the hysterectomy, ovariohysterectomy and uteropexy are recommended. This report proposes to describe the chronic pyometra surgical treatments with the uteropexy technique in mini horses that do not respond to the clinical treatment. Case: A 14-year-old mini breed horse mare weighing 117 kg was sent to Veterinarian Hospital (HV) of the Paraná Federal University (UFPR), presenting dystocia background and intrauterine purulent secretion. The clinical treatment had been conducted, but not well succeeded. An hysteroscopy was conducted with a cervix rupture monitoring, uterine mucosa edematiated and crispy, presenting liquid and a high amount of purulent secretion in the uterus horn and body. The biopsy identified uteropexy. The post-surgical complications were minimums and 30 days after the procedure the laparoscopy was repeated with uterine healing monitoring, without adherences and the uterus were at horizontal position. The hysteroscopy was conducted where a small amount of purulent secretion was perceived. Ten days after the second laparoscopy the patient was discharged. Two years after the procedure, the animal responsible informed that there was not a relapse. Discussion: the mare pyometra occurrence is uncommon and emerges by nature protection false mechanisms. Any change or flaw in one of these protection mechanics barriers, may result in a reproductive change due to uterine infection, resulting in reduction of mare reproductive capacity. Probably this reports patients developed pyometra due to the cervix lesion it's presented made easier the uterus external microorganisms entrance, that predisposes an chronic uterine infection. As many authors report, the chronic pyometra clinical treatment is not always successful, also observed in the case reported, indicating then surgical treatment. There are many pyometra surgical treatments indications as: Wedge resection technique in case of cervix adherence, uteropexy technique, ovary-hysterectomy technique or hysterectomy. The ovary-hysterectomy and the hysterectomy was not conducted for being considered highly invasive. This case choice procedure was the uteropexy, which corresponds to fixing the broad ligament of the uterus to the abdominal wall, repositioning it horizontally, to obtain a better drainage and motility, since this is your anatomic position. In the report, the surgical technique was conducted satisfactorily, certifying the uterine elevation by laparoscopy in the postoperative and also by the responsible report, that the animal does not relapse in two years. The postoperative complications were not alarming, considering that it ceased 24h after the procedure. The conclusions present in this treatment show that the hysteropexy conducted by videosurgery with toggles application developed the necessary uterine elevation to the liquid drainage, that allows the mare to execute the uterine cleaning by the physiological form. Keywords: uterus, endometritis, uteropexy, uterine elevation. Histeropexia com aplicação de “toggles” para tratamento de piometra em mini horse Descritores: útero, edometrite, uteropexia, elevação uterina.